3. Oblicze ideowe republiki i polityka historyczna współczesnego Kirgistanu .......... 69 (Kirgistan – oblicza transformacji, 2020)
THE IDEOLOGICAL IMAGE OF THE REPUBLIC AND THE HISTORICAL POLITICS OF CONTEMPORARY KYRGYZSTANIn this chapter, the author presents the importance of the Soviet period in the consciousness of the society and politicians in the current ideological situation in Kyrgyzstan. In his considerations, the author presents the attempts to create the idea of the leading Kyrgyz statehood after the collapse of the Soviet Union. The text presents ideological parallels characterized by the alternation of Kyrgyz nationalism with Soviet internationalism. Recent years have seen an attempt by the highest authorities to develop an intermediate model by combining the pre-Soviet with the Soviet heritage. In the summary, the author shows the impact of multi-ethnicity on the problem of choosing a leading idea, which is why Kyrgyzstan remains in an ideological void, which the author is trying to fill with previously functioning patterns.